In vitro bioaccessibility of alpha-linolenic acid in chicken sausages as affected by flaxseed oil incorporation method. (15th September 2022) - Bolger, Zara; Grasso, Simona; Brunton, Nigel; Moloney, Aidan P.; Hamill, Ruth; Monahan, Frank J.
Abstract: In the production of meat products fortified with omega-3 fatty acids using plant oils, different oil incorporation methods may be used to off-set potential negative effects of polyunsaturated fatty acids on the sensory quality of the products. Using flaxseed oil to deliver alpha-linolenic acid (ALA) at a level sufficient to meet the European Food Safety Authority nutrition and health claims, this study investigated the effect of the following oil incorporation methods on bioaccessibility of ALA in chicken sausages: direct oil addition (O); emulsified oil (E); freeze-dried encapsulated oil (F); freeze-dried encapsulated oil cross-linked with genipin (G); spray-dried encapsulated oil (S). Using an in vitro gastrointestinal model, the bioaccessibility of ALA from the sausages ranged between 19.2 and 33.2%, with most ALA being released in the intestinal phase. The ALA contained in (F) and (G) was more bioaccessible (p ≤ 0.05) than the O, E and S formulations, which were not significantly different from each other. Microstructural differences between formulations observed using microscopy may account for the differences in bioaccessibility. From this work it can be concluded that ALA bioaccessibility depends on the oil incorporation method, therefore this factor should be considered in the development of meat products fortified with omega-3 fatty acids. Highlights: Flaxseed oil in chicken sausages to deliver alpha-linolenic acid (ALA) at EFSA levels. Direct oil addition, emulsified oil and three types of encapsulated oil were compared. In vitro digestion measuring bioaccessibility in oral, gastric and intestinal phases. ALA in freeze-dried encapsulated formulations F and G more bioaccessible than others. Microstructural differences may account for the differences in bioaccessibility.